Spatio-temporal patterns in juvenile habitat for 13 groundfishes in the California Current Ecosystem - Tolimieri, Nick; Wallace, John; Haltuch, Melissa (PloS one, 2020)
Identifying juvenile habitats is critical for understanding a species' ecology and for focusing spatial fishery management by defining references like essential fish habitat (EFH). Here, we used vector autoregressive spatio-temporal models (VAST) to delineate spatial and temporal patterns in juvenile density for 13 commercially important species of groundfishes off the US west coast. In particular, we identified hotspots with high juvenile density. Three qualitative patterns of distribution and abundance emerged. First, Dover sole Microstomus pacificus, Pacific grenadier Coryphaenoides acrolepis, shortspine thornyhead Sebastolobus alascanus, and splitnose rockfish Sebastes diploproa had distinct, spatially-limited hotspots that were spatially consistent through time. Next, Pacific hake Merluccius productus and darkblotched rockfish Sebastes crameri had distinct, spatially limited hotspots, but the location of these hotspots varied through time. Finally, arrowtooth flounder Atheresthes stomias, English sole Parophrys vetulus, sablefish Anoplopoma fimbria, Pacific grenadier Coryphaenoides acrolepis, lingcod Ophiodon elongatus, longspine thornyhead Sebastolobus altivelis, petrale sole Eopsetta jordani, and Pacific sanddab Citharichthys sordidus had large hotspots that spanned a broad latitudinal range. These habitats represent potential, if not likely, nursery areas, the location of which will inform spatial management.